ANALYSIS OF FACTORS INFLUENCING FEB UDINUS ACCOUNTING STUDENTS' INTEREST IN BECOMING AUDITORS IN KAP - Rizki Azizah Wijayanti; Natalistyo TAH (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to test the analysis of factors that influence the interest of FEB Udinus accounting students to become auditors at the Public Accounting Firm. The population in this study were all students majoring in accounting class of 2021 who were registered at Dian Nuswantoro University. The number of samples in this research was 100 students majoring in accounting class of 2021 who were registered at Dian Nuswantoro University. The sampling technique uses a purposive sampling method. The research method used is quantitative with the data source in the form of primary data. The data analysis method uses multiple linear regression analysis with SPSS version 22. The results of this research provide evidence that partially the variables of financial rewards, professional training, social values, professional recognition and work environment have a positive effect on accounting students' interest in becoming auditors at the Public Accounting Firm.